Electronic and firepower collaborative interception decision technology in high mobility ultra short range air defense operations - HE Wei (Zhihui kongzhi yu fangzhen, 2025)
Aiming at the typical air threats faced in landing operation,this paper focuses on air situation assessment and decision model of electronics and firepower collaborative interception in process of high mobility ultra short range air defense operations. According to the relevant interception model, combat vehicle such as electronics and firepower are managed to solve the collaborative problem between firepower strike and electronic warfare,radar detection and electronic warfare, command communication and electronic warfare. Related models can achieve the combination of multiple combat vehicle.